Aksi PEGIDA Terhadap Pengungsi Muslim di Jerman - Rofiidah, Ghina Nur; Yusra, Muhammad; Dermawan, Rifki (Hubungan Internasional Universitas Andalas, 2023)
This research examines the actions of Patriotic Europeans Against the Islamization of the West (PEGIDA) towards Muslim refugees in Germany through the framework of Islamophobia as formulated by the Runnymede Trust. The study utilizes a qualitative methodology with a descriptive-analytical research design to comprehend the nature and implications of PEGIDA's anti-Muslim sentiments and actions within the broader context of the refugee crisis in Germany. The research begins by discussing the refugee crisis and the development of Islamophobia in Germany, which serves as the rationale for the rise of PEGIDA. The study identifies the main objectives of the group and the prevailing public sentiments towards Muslim refugees. Based on the Islamophobia framework, this research analyzes the ideological foundations and strategies employed by PEGIDA. The conceptual framework examines aspects of prejudice, stereotypes, and discriminatory practices faced by the Muslim community due to PEGIDA's actions, which contribute to the academic discourse on Islamophobia, right-wing movements, and refugee integration in Europe. The results of this research reveal that PEGIDA's actions, based on aspects of Islamophobia, have created divisions between the society and refugees that can lead to crimes. The government has also made several efforts to address this issue, including reapplying the Dublin Regulation and collaborating with Turkey.